2017
DOI: 10.4103/1117-6806.199964
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of PANC3 score in predicting severity of acute pancreatitis

Abstract: Introduction:Acute pancreatitis is inflammatory process of the pancreas associated with local and systemic complications. At present, there are lots of scores (such as Ransons, APACHE II, bedside index for severity in acute pancreatitis) that help us in predicting severity at the time of admission but these are time consuming or require complex calculation and are costly.Material and Methods:PANC3 Scoring System is one of the better systems because the three criteria used (hematocrit, body mass index, and pleu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 18 publications
1
6
0
1
Order By: Relevance
“…14 Ocampo et al have stated in their study that pleural effusion is superior to multiple factor scoring system in predicting acute pancreatitis outcome by likelihood positive ratio of 16.1 for predicting total complication which is statistically significant. 20 The evaluation of PANC 3 score in our study is comparable to that observed by Shah AS et al 21 , who did a study on 100 patients and found out that the sensitivity of PANC3 score was 75%, and the specificity was 96.43%. The PPV was 80%, and the NPV was 95.29% in Results of PANC 3 score were comparable with the Modified ATLANTA classification and the APACHE II score (p value -0.005, kappa value of 0.266 and p value of 0.01 respectively).…”
Section: Discussionsupporting
confidence: 87%
“…14 Ocampo et al have stated in their study that pleural effusion is superior to multiple factor scoring system in predicting acute pancreatitis outcome by likelihood positive ratio of 16.1 for predicting total complication which is statistically significant. 20 The evaluation of PANC 3 score in our study is comparable to that observed by Shah AS et al 21 , who did a study on 100 patients and found out that the sensitivity of PANC3 score was 75%, and the specificity was 96.43%. The PPV was 80%, and the NPV was 95.29% in Results of PANC 3 score were comparable with the Modified ATLANTA classification and the APACHE II score (p value -0.005, kappa value of 0.266 and p value of 0.01 respectively).…”
Section: Discussionsupporting
confidence: 87%
“…There are many scoring systems that providers may choose to utilize when making triaging decisions for this population. Some scoring systems that are available include Ranson Criteria, BISAP, PANC3, Modified CT Severity Index, Glasgow-Imrie Criteria, and the Pancreatitis Outcome Prediction score [17][18][19][20][21][22][23]. There is no single scoring system that is widely considered superior for predicting inpatient mortality with AP [24].…”
Section: Discussionmentioning
confidence: 99%
“…The combination of the three variables is highly predictive of SAP. PANC3 score has 96.43% specificity, 75% sensitivity, 80% positive predictive value, and 95.29% negative predictive value to identify severe acute pancreatitis (Shah et al, 2017). Another study showed that PANC3 score has sensitivity of 33% and specificity of 100% (Borges et al, 2017).…”
Section: Panc3 Scorementioning
confidence: 99%
“…The Ranson's criteria are used to score alcoholic pancreatitis while the modified criteria including 10 parameters are used to score gallbladder pancreatitis (Shah et al, 2017;Hagjer and Kumar, 2018;Waller et al, 2018). It has 10 parameters to assess gallstone pancreatitis.…”
Section: Modified Ranson's Criteriamentioning
confidence: 99%